UNDERSTANDING THE SOURCES OF LEARNING MATERIALS PREPARATION FOR ENGLISH CLASS DURING THE UNIVERSITY CLOSURES POLICIES DUE TO THE COVID-19 DISRUPTION IN ACEH PROVINCE - Azwar Rahmat; Resi Julita; Rasyimah Rasyimah; Dewi Kumala Sari; Yuda Septian Kurniawan (Indonesian Journal of Education (INJOE), 2023)
This paper was conducted to understand the sources of teaching materials for lecturers for the needs of students in English programs at several universities during the pandemic. The authors believe the disruption to teaching occurred resulted from the university's policy of closing campuses but continuing classes remotely. The shift to remote education has challenged lecturers in preparing teaching materials for emergency classes where lecturers have to prepare needed materials for emergency learning. More than 70 respondents took part in interviews and short surveys. The qualitative design, under a phenomenological approach, such as data coding and data interpretation, was done to meet the validity and reliability findings. The results revealed that some lecturers had experience in technology-based learning but needed to be more relaxed in handling teaching materials for poorly prepared distance classes. Few lecturers know that distance learning is more challenging than online learning. The challenge can be seen in the way the lecturers prepare teaching materials which slightly forces the lecturers to look for teaching materials in different ways. The result indicates that lecturers need more experience adapting to distance learning, as evidenced by being a little overwhelmed in obtaining and preparing teaching materials. The results of this study suggest the need for solutions to develop technology-based pedagogical exercises that make it easier for English lecturers and manage learning in difficult times such as a pandemic. Likewise, lecturers need experience responding to emergency teaching, which impacts education continuity at many Aceh universities.